A PENGARUH DIGITAL MARKETING, BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN (STUDI PEMBELIAN BATIK DI E-COMMERCE TIKTOK SHOP) - Aprian Aditama, Rizky Ramadhan; Larasati, Nike; Paramita Pratita, Mutya (Jurnal Akuntansi Dan Manajemen, 2024)
This study aims to determine the effect of digital marketing and brand image on the decision to purchase batik clothes on the TikTok shop application. This study also aims to determine the effect of consumer trust mediating the relationship between digital marketing and brand image on the decision to purchase batik clothes on the TikTok shop application. This type of research is quantitative with a sample of 100 respondents. The data collection technique used is a questionnaire. The data analysis method in this study is multiple linear regression analysis using SPSS software. The results of the study show that the digital marketing variable has a significant effect on purchasing decisions with a t-count value of 3.396> t-table 1.660, and a significance value of 0.001 <0.05. The brand image variable has a significant effect on purchasing decisions with a t-count value of 4.913> t-table 1.660. It can be concluded that by using the right digital marketing strategy, businesses can reach more consumers, build relationships with them, and encourage them to buy their products or services. By using digital marketing effectively, businesses can increase their sales and profits. Businesses can use a variety of strategies to build a positive brand image, such as providing high-quality products or services, providing good customer service, and building effective communication with consumers.